Pulmonary congestion during exercise stress echocardiography in ischaemic, heart failure and valvular patients. (14th October 2021) - Merli, E; Zagatina, A; Merlo, P.M; Arbucci, R; Borguezan Daros, C; De Castro E Silva Pretto, J.L; Amor, M; Morrone, D; D'Andrea, A; Reisenhofer, B; Rodriguez-Zanella, H; Wierzbowska-Drabik, K; et al.
Abstract: Background: Lung ultrasound (LUS) detects pulmonary congestion as B-lines at rest and exercise stress echocardiography (ESE). Aim: To assess the prevalence of B-lines during ESE in different cardiovascular diseases. Methods: We performed ESE plus LUS (4-site simplified scan) in 4419 subjects referred for semi-supine bike ESE in 28 certified centers. B-lines score ranged from 0 (normal) to 40 (severely abnormal). Stress B-lines abnormal result was ≥2 units. Six different populations were evaluated: healthy controls (n=103); chronic coronary syndromes (CCS, n=3701); heart failure with reduced ejection fraction (HFrEF, n=395); heart failure with preserved ejection fraction (HFpEF, n=70); valvular heart disease (VHD) for ischemic mitral regurgitation ≥moderate at rest (n=123); repaired tetralogy of Fallot (ToF, n=27). Results: Feasibility of B-lines was 100% at rest and peak ESE in all subjects. Imaging and analysis time were <1 minute. B-lines (median) were not detectable in healthy subjects (rest=0.1 [0–1] vs 0.1 [0–1], p=ns) and TOF (rest=0.2 [0–2] vs 0.3 [0–4], p=ns), but were present in all other groups: see figure. During ESE, B-lines increased in CCS (rest=0.5 [0–24] vs ESE=1.3 [0–28], p<0.001); HFrEF (rest=1.4 [0–35] vs ESE=2.9 [0–40], p<0.001); HFpEF (rest=0.3 [0–2] vs ESE=3.4 [0–12], p<0.001), VHD (rest=1.7 [0–12] vs ESE=4.3 [0–23], p<0.001). Stress B-lines were correlated with stress-rest change in wall motion score index in CCS (r=0.325, p<0.001), contractile reserve in HFrEF (r=−0.266, p<0.001) and in VHD (r=−.0300, p=0.001), left atrial volume stress-rest change in HFpEF (r=0.287, p=0.043). Conclusion: B-lines identify the pulmonary congestion phenotype at rest and more frequently during ESE in patients with different coronary, myocardial or valvular heart disease, all sharing the final common pathway of acute backward left heart failure through different disease-specific mechanisms. B-lines are absent in healthy subjects and in conditions inducing a mostly right-sided overload such as repaired ToF. Funding Acknowledgement: Type of funding sources: None.